Evaluation in vitro of plant extracts spiked with nanoparticles for the control of Fusarium oxysporum - Cerna-Chávez, Ernesto; Malacara-Herrera, Irasema del Rosario; Ochoa-Fuentes, Yisa María; Hernández-Juárez, Agustín (Ecosistemas y Recursos Agropecuarios, 2023)
Fusarium oxysporum, causing wilting and root rot. The objective of the work was to evaluate in vitro extracts of Larrea tridentata L. to dose (10, 100, 500, 1 000, 3 000 y 5 000 ppm) and mustard Sinapis alba L. with two aditional concentration of 1 500 y 2 000 ppm with silicon oxide and zinc oxide at doses of: 1, 3 y 5% nanoparticles on mycelial growth and sporulation of F. oxysporum of garlic. Inhibitory concentrations and the number of conidia were determined. Data were analyzed by Probit analysis, ANOVA and Tukey’s test. The results indicated that governor and mustard extracts with SiO2, presented better inhibitory effect on mycelial growth, and significant reduction in sporulation was observed, unlike the extracts added with ZnO. SiO2 nanoparticles with governor and mustard extracts are effective for in vitro management of F. oxysporum.